Rapid and Sensitive Identification of Bacterial Infection and Bacteria Gram Types in Pleural Fluid of Children. (30th January 2015) - Wu, Yi-Dong; Li, Wei; Wei, Yi; Gao, Hui-Hui; Shang, Shi-Qiang; Du, Li-Zhong
Real-time polymerase chain reaction (RT-PCR) techniques have been increasingly used to detect microbial DNA in clinic for the diagnosis of bacterial infection. This study aims to developing an RT-PCR method to detect bacteria in pleural fluid (PF). We performed a method to simultaneously detect and classify the clinically relevant bacterial pathogens in hydrothorax with Gram probe RT-PCR (GRT-PCR), which targets the conserved region of the 16S rRNA gene. Our results showed this method could specifically and correctly identify 14 clinically important bacterial strains in hydrothorax including 7 gram-positive and 7 gram-negative bacteria. And the sensitivity of this GRT-PCR method in serial dilution can reach 10 CFU/mL. In clinical trial, 180 PF samples from children who were clinically suspected to suffer from bacterial pneumonia and empyema were collected. These samples were detected by GRT-PCR, standard culture, and biochemical routine analysis. The positive rate of the GRT-PCR array was 17.78% (32/180), significantly higher than that of PF culture (11.67%; 21/180; P = .003). When PF culture was used as control, the sensitivity of GRT-PCR was 95.24% (95% confidence interval = 74.13-99.75), and the specificity was 92.45% (95% confidence interval = 86.89-95.86). Our study showed that GRT-PCR is a more effective method for rapid, sensitive, and specific diagnosis of bacterial infection in hydrothorax compared with other traditional methods.